Women Protection and Decision of Customary Justice on The Ride of Cross Action (Women Protection Based On Law And Customary Justice In Atambua) - Siti Syahida Nurani; Absori Absori; Khudzaifah Dimyati; Kelik Wardiono; Wafda Vivid Izziyana (Sociological Jurisprudence Journal, 2019)
Rape can be occured in all women from all side of life, occupations, age, and marital status, which was done alone or abuzz. The perpetrators of violence also come from various circles, work, age, social class and marital status. In this case, the number of women violence against in Atambua is quite high. Sexual abuse cases and sexual harassment turned out most of the perpetrators are still related to blood with victims, such as biological father, siblings, uncle and neighbors. The cases of sexual assault against women in Atambua are resolved in customary. However, any form of resolution, the act of violence of rape against viewed from various aspects still must be responded as a criminal act, for example the custom settlement of tallitan tafani still apply penal sanction in the form of penalty as one of the effort of restoration of good name, and also dignity for the victim.